Simple atomic and molecular systems : new results and applications - Oks, E. A. (Evgeniæi Aleksandrovich) (IOP (Series). Release 21., 2021)
Simple atoms are atoms consisting of no more than three particles. They are the test-bench of atomic physics and quantum mechanics. This book presents these findings, bridging the gap between textbook descriptions of these systems and the latest research. Counterintuitive phenomena in simple atomic and molecular systems are revealed, along with their fundamental importance and practical applications. These include the advanced methods for lasing in the infra-red and microwave ranges, the improved design of x-ray lasers, and advanced methods for spectroscopic diagnostics of plasmas. The analytical solutions of simple atoms and their role in theoretical physics will also be discussed. The book is aimed at graduate students and researchers in the field of atomic and molecular physics.